Acceptance, quality and trust factors –conceptual model for open government data potential use - Zainal, Noor Zalina; Hussin, Husnayati; Mior Nazri, Mior Nasir (IIUM Press, International Islamic University Malaysia, 2019)
To implement Big Data extensively in the public sector, many governments around the world are taking their initiative to ensure that Open Government Data (OGD) is a success. Even though the governments had provided thousands of datasets in the open data website, the level of use of open government data is still a question that has not been resolved. Therefore, the objective of this paper is to propose a new model of measuring the level of use of open government data. By integrating the Unified Theory of Acceptance and Use of Technology (UTAUT), IS Success Model (ISSM) and Trust factors, this new model perhaps can be a major contribution to the governments in ensuring that citizens are getting benefits from the datasets provided in the open data website.